Cellular basis for rod-cone interactions in the outer retina - Križaj, David (Zdravniški vestnik, 2002)
Background. At least twice daily our retinas move between a light adapted, cone-dominated (photopic) state and a dark-adapted, color-blind and highly light-sensitive roddominated (scotopic) state. In between is a rather ill-defined transitional state called the mesopic state in which retinal circuits express both rod and cone signals. Consequently, in the mesopic statethe retinal output to the brain contained in the firing patterns of the ganglion cells consists of information derived from both rod and cone signals.Morphology, physiology and psychophysics all contributed to an understanding that the two systems are not independent but interact extensively via both pooling and mutual inhibition. This review lays down a rationale for such rod-cone interactions in the vertebrate retinas. It suggests that the important functional roles of rod-cone interactions is in that they shorten the duration of the mesopic state. As a result, the retina is maintained in either in the (rod-dominated) high sensitivity photon counting mode or in the second mode which emphasizes temporal transients and spatial resolution (the cone-dominated photopic state). Conclusions. Experimental evidence for pre- and postsynaptic mixing of rod and cone signalsin the retina is shown together with the preeminent neuromodulatory role of both light and dopamine in controling inter-actions between rod and cone signals. Dopamine is shown to be both necessary and sufficient to mediatelight adaptation in the retina.
Keywords: adaptacija; Adaptacija očesna; Adaptation, ocular; Cones (retina); Čepki (mrežnica); Dopamin; Dopamine; Electroretinography; Elektroretinografija; fiziologija; Fotoreceptorji; oftalmologija; Paličice (mrežnica); Photoreceptors; Rods (retina); vid